Community structure analysis of soil insects and their potential role as bioindicators in various ecosystem types in Lombok, West Nusa Tenggara, Indonesia - immy rohyani (Society for Indonesian Biodiversity, 2020)
Abstract. Rohyani IS. 2020. Community structure analysis of soil insects and their potential role as bioindicators in various ecosystem types in Lombok, West Nusa Tenggara, Indonesia. Biodiversitas 21: 4221-4227. Various types of ecosystems can be found in Lombok, with the dominant ecosystems are natural forest, mangrove, mixed garden, rice field, and mining. These ecosystems have a high level of biodiversity and unique flora and fauna communities, including soil insects that partake in the process of ecosystem energy flow. This study aimed to analyze the community structure of soil insects and their potential role as bioindicators in five types of dominant and unique ecosystems in Lombok island. The data collection was done using pitfall traps, yellow pan traps, baited pitfall traps, soil sampling, and litter collection. The findings revealed that there are 60,439 individuals, 79 families, and 16 orders of insects in various types of ecosystems. Diversity ??(H') and evenness (E) index values ??for family level in all ecosystem types are low on average (H'=0.76 and E=0.10). Cerambycidae (Coleoptera), Trichogrammatidae (Hymenoptera), and Cicindelidae (Coleoptera) are a potential bioindicator in the forest, in the mangrove, and in the rice field ecosystems, respectively. However, the potential bioindicator could not be found since the distribution of the family is almost even in the garden ecosystem. The Tenebrionidae (Coleoptera) and the Acroceridae (Diptera) are soil insects with relatively high abundance and are found only in the mining ecosystems.